UMPSA supports STEM-encouraged school students in Tuaran - Nur Hartini, Mohd Hatta (UMPSA, 2024)
TUARAN, 1 March 2024 - The management of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) provided support to school students and encouraged STEM learning involving Kampung Kiwatu, Kampung Batangan, Kampung Roun, and Kampung Serusop and surrounding areas of Tuaran, targeting efforts to inspire young people and B40 students.